High impedance fault location in 11 kV underground distribution systems using wavelet transforms - Bakar, Ab Halim Abu; Ali, M.S.; Tan, Chia Kwang; Mokhlis, Hazlie; Arof, Hamzah (Elsevier, 2014)
Detecting and locating high impedance fault (HIF) in distribution system is a crucial task. HIF causes insulation degradation and over time will lead to supply interruptions. However, it is quite challenging to locate HIF since changes of voltage or current signal during the fault is insignificant and not able to trigger protection system. Besides, the complexity of the distribution system such as non-homogenous line and lateral with branches increase the difficulty in detecting and locating HIF. Considering these issues, this paper presents a method to detect and locate HIF based on Discrete Wavelet Transform (DWT) Multi-Resolution Analysis. In the method, fault features from voltages measured at primary substation are extracted using DWT and matched with the pre-developed database from simulation. Due to single measurement and multiple branches, the matching will produce multiple possible faulted sections. This problem is then solved by applying ranking analysis to rank the possible faulted sections from the most likely to the least likely faulted section. The proposed method has been tested with all types of faults on a 38-node distribution network system in Malaysia using the PSCAD/EMTDC software. The test results revealed the effectiveness of the method. Since only single measurement of voltage signal is needed, the method is considered economical for practical implementation.